2005
DOI: 10.3201/eid1104.040178
|View full text |Cite
|
Sign up to set email alerts
|

Reemergence of CanineEchinococcus granulosusInfection, Wales

Abstract: A survey of 2 Welsh counties found that canine echinococcosis has reemerged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 12 publications
1
28
1
2
Order By: Relevance
“…A number of studies have also found that older dogs had a lower probability of positivity than younger dogs (Sharifi and Zia-Ali, 1996;Buishi et al, 2005a;Buishi et al, 2006;Acosta-Jamett et al, 2010a;Inangolet et al, 2010), which may suggest some degree of acquired immunity, or may indicate age-related variation in dog behaviour or management (Torgerson et al, 2003b;Torgerson, 2006a). A lack of knowledge about echinococcosis and a lack of recent praziquantel dosing have also been identified as associated with an increased probability of positivity (Buishi et al, 2005a;Buishi et al, 2005b;Huang et al, 2008;Acosta-Jamett et al, 2010a). …”
Section: Risk Factors For Echinococcosis In Domestic Animalsmentioning
confidence: 89%
“…A number of studies have also found that older dogs had a lower probability of positivity than younger dogs (Sharifi and Zia-Ali, 1996;Buishi et al, 2005a;Buishi et al, 2006;Acosta-Jamett et al, 2010a;Inangolet et al, 2010), which may suggest some degree of acquired immunity, or may indicate age-related variation in dog behaviour or management (Torgerson et al, 2003b;Torgerson, 2006a). A lack of knowledge about echinococcosis and a lack of recent praziquantel dosing have also been identified as associated with an increased probability of positivity (Buishi et al, 2005a;Buishi et al, 2005b;Huang et al, 2008;Acosta-Jamett et al, 2010a). …”
Section: Risk Factors For Echinococcosis In Domestic Animalsmentioning
confidence: 89%
“…The number of dogs owned, frequency of contact with dogs, feeding of dogs with infected offal, allowing dogs to roam free, infrequent administration of praziquantel to dogs, and contaminated sources of drinking water have all been reported as possible risk factors for E. granulosus transmission [1,2,10]. The objective of this study was to describe the clinical features of hepatic and abdominal CE patients treated in referral hospitals in Dhaka, Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…15 Human CE remains endemic in the UK, but incidence has dropped over the last 40 years, in part due to directed interventions in mid-Wales, but also because of improvements in sheep-dog management and wide availability of praziquantel-based dewormers. 7,16,17 Nevertheless, sporadic autochthonous human CE cases continue to occur both in the midWales endemic zone as well as occasionally in apparent low-risk regions of England including southwest counties. In 2011, there were 174 hunts listed in England and Wales with fox-hound numbers from 20 to .100.…”
Section: Discussionmentioning
confidence: 99%